Discrete Time Flowing and A Contradiction to Einsteins Assumptions (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Due to the limited velocity of light, there is a time duration to propagate a light ray between any two distinct spacetime points in the universe. Upon that argument, authors attempt is to obtain a very specific result that may useful for the Cosmology subject fields, string theory and the Astronomy subject fields. The final result implies that the time flowing depends on the space time location and time flowing is a relative fact in the universe.Time flowing is a relative fact does not mean the notion in the Special theory of Relativity regarding the relativity in the time.